Mapping the public sector diaspora: towards a model of inter-sectoral cultural hybridity using evidence from the English healthcare reforms - Waring, Justin (Wiley-Blackwell, 2015)
Public service reforms increasingly blur the boundaries between public and private sectors, involving hybrid modes of service organization. With growing numbers of public services being transferred to private or mutual ownership, the article interprets reform as a public sector diaspora. Drawing upon the diaspora studies literature, the article proposes a model of hybridization that centres on the possibilities for cultural dislocation, adaptation, and hybridity. Focusing on reforms within the English National Health Service, the article presents an ethnographic study of the transfer or diaspora of doctors, nurses, clinical practitioners, and healthcare assistants from a public hospital to a private healthcare provider, exploring their experiences of migration, resettlement, and cultural hybridity. The model addresses a conceptual gap within the public policy and management literature by elaborating the antecedents, processes, and forms of cultural hybridization.